2015
DOI: 10.5507/bp.2014.058
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal free light chains in cerebrospinal fluid as markers of intrathecal inflammation. Comparison with oligoclonal IgG

Abstract: Aims.To compare the sensitivity and specificity of CSF-restricted oligoclonal IgG and free light chains as markers of multiple sclerosis and other inflammatory neurological diseases. Methods. 196 paired CSF and serum samples were examined for oligoclonal IgG and oligoclonal free light chains. The sensitivity and specificity of the tests were calculated and optimal cut-offs for the number of CSF-restricted oligoclonal bands were then determined by analysis of receiver operating characteristic curves. Results. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 66 publications
3
20
0
5
Order By: Relevance
“…5 Nevertheless, we proved that CSF fLC quantitation can predict intrathecal fLC synthesis. Although we did not aim at diagnosis-related analysis, it is of note that two patients with CNS inflammation proved positive for both o-fLC, while negative for o-IgG; 19/20 patients with MS or CIS (95%) were both o-IgG and o-fKLC positive and 17 (85%) were also o-fLLC positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Nevertheless, we proved that CSF fLC quantitation can predict intrathecal fLC synthesis. Although we did not aim at diagnosis-related analysis, it is of note that two patients with CNS inflammation proved positive for both o-fLC, while negative for o-IgG; 19/20 patients with MS or CIS (95%) were both o-IgG and o-fKLC positive and 17 (85%) were also o-fLLC positive.…”
Section: Resultsmentioning
confidence: 99%
“…5 Samples were then kept frozen at À30 C until quantitative fLC measurements. CSF and serum fKLC and fLLC concentrations were determined on the SPA Plus turbidimetric analyser using dedicated Freelite TM kits (The Binding Site Ltd.) CE marked for CSF analysis (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…For oligoclonal fLC detection, an aliquot was kept at +2 to +8°C for up to 20 days. We have previously reported that oligoclonal fLC patterns remain stable during this period [37]. …”
Section: Methodsmentioning
confidence: 99%
“…After we had succesfully introduced oligoclonal fLC detection [36, 37], we looked for a quantitative method for comparison and possibly monitoring purposes. Our sandwich ELISA, which was developed during several years, is based on the same principle as the o-fLC test [38].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 ), IgD (ref. 7 ) and free light chains [8][9][10] detection was reported to provide useful additional information. The concentration of IgG in CSF lies between 10 -100 mg/L and IgG can be easily detected by means of chromogenic detection method.…”
Section: Introductionmentioning
confidence: 99%